Androgenetic alopecia in a 9-year-old child. - Chieco, P. (European Journal of Pediatric Dermatology, 2016)
A careful family and personal history, physical examination of the hair and of the remaining skin and genital area, a non-invasive test like trichoscopy are sufficient to rule out other causes of thinning hair in the child, such as alopecia areata, trichotillomania, congenital triangular alopecia, hereditary diseases, telogen effluvium. In our case we did not test dehydroepiandrosterone sulfate (DHEA-S) because to unveil adrenarche in a 9-year-old boy is not clinically relevant. Androgenetic alopecia in our case was of the female type with central thinning without recession of the hairline as already reported in the literature (3). The response to minoxidil 2% was significant already after the first months of treatment. In children the drug is not recommended because there are no studies at this age; however, side effects, such as hypertrichosis (1) or hypotension (2) are still outstanding.